If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.75(4x + 8) = -3 Reorder the terms: 0.75(8 + 4x) = -3 (8 * 0.75 + 4x * 0.75) = -3 (6 + 3x) = -3 Solving 6 + 3x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = -3 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = -3 + -6 3x = -3 + -6 Combine like terms: -3 + -6 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| 5k-15+j=3j-5 | | 3(2g+7m)= | | (x+x)-20x+100=0 | | 0.2r=-8 | | v+53=3v+21 | | 9=5.4*x | | 5y^2+7y-4=0 | | 12-4p=-4(-5p-3) | | (5x-15)=what | | 5y-2=3x+2 | | 4(-2f-6g)= | | 3x=2.52 | | 140=4x^2-4+4-16 | | x^1000=0.9 | | 3y=-x+0 | | 13w+16w-7+5=-5w+5-7 | | 4x^2-156=0 | | 8(-4k-4)=-5k-32 | | 3(3+2j)= | | 3z-35=5z-87 | | 5m-13=n+5 | | u=2u-74 | | x=7x+6y | | 3q-70=q+26 | | (x+3)*5-5=20 | | 2(5+3q)= | | 9w-7=8w-4 | | 2x^2+1=129 | | 5(y+7)=7*y+35 | | -2+5v=-27 | | 296.64=160+0.56x | | -2(3+9x)= |